Elucidation of carbohydrate molecular interaction mechanism of recombinant and native ArtinM - Giménez-Romero, David; Bueno, Paulo Roberto [UNESP]; Pesquero, Naira C. [UNESP]; Monzó, Isidro S.; Puchades, Rosa; Maquieira, Ángel (American Chemical Society (ACS), 2013)
The quartz crystal microbalance (QCM) technique has been applied for monitoring the biorecognition of ArtinM lectins at low horseradish peroxidase glycoprotein (HRP) concentrations, using a simple kinetic model based on Langmuir isotherm in previous work.18 The latter approach was consistent with the data at dilute conditions but it fails to explain the small differences existing in the jArtinM and rArtinM due to ligand binding concentration limit. Here we extend this analysis to differentiate sugar-binding event of recombinant (rArtinM) and native (jArtinM) ArtinM lectins beyond dilute conditions. Equivalently, functionalized quartz crystal microbalance with dissipation monitoring (QCM-D) was used as real-time label-free technique but structural-dependent kinetic features of the interaction were detailed by using combined analysis of mass and dissipation factor variation. The stated kinetic model not only was able to predict the diluted conditions but also allowed to differentiate ArtinM avidities. For instance, it was found that rArtinM avidity is higher than jArtinM avidity whereas their conformational flexibility is lower. Additionally, it was possible to monitor the hydration shell of the binding complex with ArtinM lectins under dynamic conditions. Such information is key in understanding and differentiating protein binding avidity, biological functionality, and kinetics. © 2013 American Chemical Society.
Keywords: Combined analysis; Concentration limits; Conformational flexibility; Dissipation factors; Horse-radish peroxidase; Label-free techniques; Quartz crystal microbalance techniques; Quartz crystal microbalance with dissipation monitoring; Biochemistry; Kinetic parameters; Kinetic theory; Proteins